Latent variable analysis and partial correlation graphs for multivariate time series - Roland Fried; Vanessa Didelez (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
We investigate the possibility of exploiting partial correlation graphs for identifying interpretable latent variables underlying a multivariate time series. It is shown how the collapsibility and separation properties of partial correlation graphs can be used to understand the relation between a factor model and the structure among the observable variables.
Keywords: 519; Time series analysis; Dimension reduction; Factor analysis; Partial correlations; Multivariate Analyse; Zeitreihenanalyse; Theorie; Korrelation